Molecular Docking Study of Catecholamines and [4-(Propan-2-yl) Phenyl]Carbamic acid with Tyrosine Hydroxylase - Parveen, Zahida; Sulaman Nawaz, Muhammad; Shakil, Shazi; H. Greig, Nigel; A. Kamal, Mohammad (CNS & Neurological Disorders - Drug Targets, 2012)
Parkinson's disease is a major age-related neurodegenerative disorder. As the classical disease-related motor symptoms are associated with the loss of dopamine-generating cells within the substantia nigra, tyrosine hydroxylase (TH), the rate-limiting enzyme in the synthesis of catecholamines has become an important target in the development of Parkinson's disease drug candidates, with the focus to augment TH levels or its activity. By contrast, TH inhibitors are of relevance in the treatment of conditions associated with catecholamine over-production, as occurs in pheochromocytomas. To aid characterizing new drug candidates, a molecular docking study of catecholamines and a novel hypothetical compound [4-(propan-2-yl) phenyl]carbamic acid (PPCA) with TH is described. Docking was performed using Autodock4.2 and results were analyzed using Chimera1.5.2. All the studied ligands were found to bind within a deep narrow groove lined with polar aromatic and acidic residues within TH. Our results corroborated a ‘hexa interacting amino acids unit’ located in this deep narrow groove crucial to the interaction of PPCA and the studied catecholamines with TH, whereby the ‘His361-His336 dyad’ was found to be even more crucial to these binding interactions. PPCA displayed a binding interaction with human TH that was comparable to the original TH substrate, L-tyrosine. Hence PPCA may warrant in vitro and in vivo characterization with TH to assess its potential as a candidate therapeutic.
Keywords: docking study